Pengaruh Leverage Dan Ukuran Perusahaan Terhadap Konservatisme Akuntansi Pada Perusahaan Manufaktur Subsektor Makanan Dan Minuman Di Bursa Efek Indonesia Tahun 2017-2021 - Rini Adel Asmara; Gerry Hamdani Putra (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
Accounting conservatism is a precautionary concept that really needs to be considered in accounting for financial statements because company activities are accompanied by uncertainty. This study aims to determine the effect of leverage (X1) and company size (X2) on accounting conservatism in food and beverage companies on the Indonesia Stock Exchange. The data source used in this research is secondary data in the form of annual financial reports. The population used in this study were all food and beverage companies listed on the Indonesia Stock Exchange (www.Idx.co.id) in 2017-2021 which were selected using purposive sampling. The number of samples used in the study were 11 companies. The analytical method used is multiple regression analysis. Based on the test results it was found that leverage had a positive and significant effect on accounting conservatism in food and beverage sub-sector manufacturing companies on the Indonesia Stock Exchange and company size had a negative and significant effect on accounting conservatism in food and beverage sub-sector manufacturing companies on the Indonesia Stock Exchange.